Cancer in the elderly in an equatorial area: French Guiana. (June 2012) - Droz, Jean-Pierre; Cenciu, Béatrice; Lopoh, Achille; Guillier, Audrey; Bianco, Laure; Fayette, Jérôme; Boyle, Helen; Terret, Catherine; Couppié, Pierre
Little information is available on the management of cancer in equatorial areas, and specifically the management of elderly cancer patients. We have retrospectively reviewed the clinical files of 71 patients older than 70 years with cancer who were treated in the Cayenne Hospital in French Guiana. The population is that of an equatorial country with the health organization of a European country. We found that oncogeriatric evaluation was feasible but is far from being routinely used. The selection of screening tools of frailty is likely to be useful in making decisions for these patients. However, specific problems are emerging: cultural mediation; low income; illegal immigrants; comorbidities; specific tropical diseases; and the incidence of HIV, human T-lymphotropic virus Type 1 and hepatitis infections. This led us to expand the study to the whole cancer patient population and to implement specific information in the database used for follow-up. These preliminary observations should be relevant for other countries.